Plantas medicinais em feiras e mercados públicos da região metropolitana de Belém do Pará, Brasil - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2015)
In the Amazon region, traditional markets have important social and symbolic functions related to the use of medicinal plants. This research examines the diversity of medicinal plants sold at fairs and public markets in the metropolitan area of Belém, as well as understanding the process of commercializing these products. We interviewed 25 merchants in 15 markets, covering four counties. Data were analyzed qualitatively and quantitatively through the Shannon-Wiener diversity indices, Sørensen similarity and Cultural Salience. One hundred sixty seven ethnospecies were recorded, distributed in 147 genera and 69 families, with Fabaceae, Asteraceae and Lamiaceae being the most representative of the families. The greatest diversity of species occurred in the city of Ananindeua, while most species similarity was found between the cities of Ananindeua and Marituba, both featuring high species richness. The greatest cultural salience indices belong to Dalbergia monetaria L.f. (verônica), Stryphnodendron sp. (barbatimão) and Myracrodruon urundeuva Allemão (aroeira). Among the resources that were sold, leaves and bark predominate, and trees and herbs were the most expressive life forms. Herbalists of Belém are the main suppliers of raw materials to the markets studied, with the Brazilian Northeast, South and Southeast contributing to the diversity of species encountered in these markets.
Ethnobotany of medicinal plants on public markets in the metropolitan region of Belém do Pará, Brazil
Keywords: Plantas medicinais; Etnobotânica urbana; Medicina popular; Mercados tradicionais; Comercialização; Belém - Pará; Pará - Estado; Região Amazônica; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA